Developing major histocompatibility markers in a species of concern: the Sacramento perch Archoplites interruptus. Issue 5 (19th September 2014) - Lavretsky, P.; Schwartz, R. S.; Baerwald, M. R.; May, B.
<x xml:space="preserve">Abstract</x> Primers targeting two non‐neutral major histocompatibility complex (mhc) II β genes were developed and assayed across several disjoint Sacramento perch Archoplites interruptus sampling locations. Variability at the two mhc loci among sampling stocks strongly correlated to previous estimates with neutral markers, suggesting that the effect of genetic drift was not limited to neutrally evolving regions of the genome. The novel mhc primers will help develop admixture schemes in A. interruptus captive breeding programmes and will increase the success of future reintroductions of this species of concern.